Oxytocin alleviates hepatic ischemia-reperfusion injury in rats - YEGEN, BERRAK; ERCAN, FERİHA; YEGEN, ŞEVKET CUMHUR (ELSEVIER SCIENCE INC, 2008)
Various mechanisms have been proposed for the pathogenesis of postischemic hepatic injury, including the generation of reactive oxygen metabolites. Oxytocin (OT) possesses antisecretory, antiulcer effects, facilitates wound healing and has anti-inflammatory properties. Hepatic ischemia-reperfusion (I/R)-injury was induced by inflow occlusion to median and left liver lobes (similar to 70%) for 30 min of ischemia followed by 1 h reperfusion in female Sprague-Dawley rats under anesthesia. I/R group (n = 8) was administered intraperitoneally either OT (500 mu g/kg) or saline at 24 and 12 h before I/R and immediately before reperfusion. Sham-operated group that underwent laparotomy without hepatic ischemia served as the control. Rats were decapitated at the end of reperfusion period. Hepatic samples were obtained for the measurement of myeloperoxidase (MPO) activity, malondialdehyde (MDA), glutathione (GSH) and collagen levels and histopathological analysis. Tumor necrosis factoralfa (TNF-alpha) and transaminases (SGOT, SGPT) were assayed in serum samples. I/R injury caused significant increases in hepatic microscopic damage scores, MPO activity, collagen levels, transaminase, serum TNF-alpha levels. Oxytocin treatment significantly reversed the I/R-induced elevations in serum transaminase and TNF-alpha levels and in hepatic MPO and collagen levels, and reduced the hepatic damage scores. OT treatment had tendency to abolish I/R-induced increase in MDA levels, while GSH levels were not altered. These results suggest that OT has a protective role in hepatic I/R injury and its protective effect in the liver appears to be dependent on its inhibitory effect on neutrophil infiltration. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: liver; ischemia/reperfusion injury; TNF-alpha; oxytocin; neutrophils; NEUTROPHIL-DEPENDENT MECHANISM; ATRIAL-NATRIURETIC-PEPTIDE; ISCHEMIA/REPERFUSION INJURY; GROWTH-HORMONE; KUPFFER CELLS; TISSUE-INJURY; RECEPTOR; INFLAMMATION; INTERLEUKIN-1; VASOPRESSIN